The silence of the cellphones. - Schneider, D.
You're enjoying a rare bit of peace and quiet, perhaps dozing on a train, when someone begins a loud cellphone conversation nearby. Electromagnetic countermeasures are available to reclaim the silence, but for the most part they are illegal. In the United States, for example, only federal agents can legally use signal jammers to block cellular communications by transmitting interfering signals. Even state prison officials, who want jammers to prevent inmates from talking on contraband cellphones, are barred from using them.